Microbiome analysis reveals potential for modulation of gut microbiota through polysaccharide-based prebiotic feeding in Oreochromis niloticus (Linnaeus, 1758) - Bera, Asit Kumar; Chowdhury, Hemanta; Ghatak, Sandeep; Malick, Ramesh Chandra; Chakraborty, Nabanita; Chakraborty, Hirak Jyoti; Swain, Himanshu Sekhar; Hassan, M. A.; Das, Basanta Kumar (Frontiers in Physiology, 2023)
Characterization and functional profiling of the gut microbiota are fundamental for guided nutritional intervention in fish and attaining favorable host-microbe interactions. Therefore, we undertook the study to explore and document the gut microbial community of Oreochromis niloticus and also to evaluate the effects of a polysaccharide-based prebiotic on the gut microbiome through a genomic approach. The Illumina HiSeq 2500 was used to amplify and sequence the V3-V4 region of 16S rRNA. A total of 1,000,199 reads were used for OTU pick up and out of 8894 OTUs, 1181 OTUs were selected for further analysis. Results revealed that Planctomycetes, Firmicutes, Proteobacteria, Verrucomicrobia, Actinobacteria and Fusobacteria were the dominant at phylum level in all the samples (control and treatment). Treatment in higher doses of prebiotics was found to improve Planctomycetes and Firmicutes while decreasing Proteobacteria and Verrucomicrobia. The enhancing trends were recorded at Bacilli, Bacillacea, and Bacillus bacteria at the class, family, and genus levels, respectively, in a dose-dependent manner. The results were consistent with conventional colony count findings, with Bacillus being more prevalent in prebiotic supplemented groups. Further, predicted functional analysis using PICRUSt suggested a dose dependent upregulation for glycolysis V, superpathway of glycol metabolism and degradation, glucose and xylose degradation, glycolysis II, and sulfoglycolysis pathways. Most of the energy, protein and amino acid synthesis pathways were found to be upregulated at lower dose of prebiotic treatment only. The findings also indicated the possibility of rationalizing gut microbiome of O. niloticus through nutritional intervention with plant based polysaccharide for optimum growth performance in commercial fish.